Androgen deprivation therapy is associated with decreased second primary lung cancer risk in the United States veterans with prostate cancer - Kyungsuk Jung; Jong Chul Park; Hyunseok Kang; Johann Christoph Brandes (Epidemiology and Health, 2018)
OBJECTIVES We investigated whether androgen deprivation therapy (ADT) in prostate cancer patients was associated with a decreased risk for second primary lung cancer in US veterans. METHODS Prostate cancer diagnoses in the US Veterans Affairs Cancer Registry between 1999 and 2008 were identified. Use of hormonal therapy and diagnoses of second primary lung cancer were determined from the registry. Synchronous prostate and lung cancers, defined as 2 diagnoses made within 1 year, were excluded from the analysis. Cancer-free survival was estimated using the Kaplan-Meier method and hazard ratios were estimated using Cox proportional hazard models. RESULTS Among the 63,141 identified patients with prostate cancer, 18,707 subjects were eligible for the study. Hormonal therapy was used in 38% of patients and the median follow-up period was 28 months. ADT use was associated with longer lung cancer-free survival in prostate cancer patients (log-rank p=0.01). After adjusting for age, race, smoking and prostate cancer stage, ADT use was associated with decreased lung cancer risk by 15, 21, and 24% after 1, 2, and 3 years, respectively. CONCLUSIONS ADT in prostate cancer patients may be associated with decreased second primary lung cancer risk among US veterans.